Development of a qualitative data analysis codebook for peri‐ictal behavior in suspected functional seizures - Higson, Lana; Finnin, Natasha; Nurse, Ewan; Cook, Mark J.; Winton‐Brown, Toby; Rayner, Genevieve; Coleman, Honor (Epilepsia (Copenhagen), 2025)
Factors that can precipitate and/or prolong functional seizure events are often challenging to identify. We aimed to develop a methodology to investigate peri-ictal behaviors in subjects experiencing functional seizures and those around them in their home environment. We conducted an iterative, four-phase process to develop a codebook for operationalizing peri-functional seizure behavior that involved observation of 37 functional seizures across 14 participants in the pre-ictal, ictal, and post-ictal phases. First, researchers reviewed and discussed the literature to devise a conceptual framework. Second, an initial codebook was drafted and refined using a test case. Third, a multi-disciplinary panel provided feedback on the coding of three further cases to further refine code definitions. Finally, the drafted codebook was piloted on 20 functional seizure events, and a discrepancy analysis was conducted. Additional exploratory analyses were conducted with the pilot data, including a correlation analysis between the number of individuals present during pre-ictal and ictal phases and seizure duration. The final codebook identifies five main factors for observers to note across the pre-ictal, ictal, and post-ictal phases of a functional seizure: body position, activity, behavior, nature of interaction, and number of bystanders; detailed definitions of the relevant subcodes are provided. Early exploratory analyses found that the more people present during the ictal phase, the longer the functional seizure tended to be (r = .61, p = .004). This is the first study to highlight the feasibility of investigating functional seizure peri-ictal behavior in a home environment, offering unique benefits to capture naturalistic social factors potentially related to seizure activity. The codebook can be validated in larger datasets to improve our understanding of how peri-ictal behavior impacts functional seizures; compare findings across studies; and inform the development of evidence-based seizure management strategies for individuals and their carers.